CLINICAL FEATURES OF THE HYPERMOBILITY SYNDROME - Sezai Şahin,; Vural Kavuncu, (Archives of Rheumatology, 2001)
Hypermobility is a clinical syndrome, which is characterized by excessive movement of the joints without a demonstratable relationship with a systemic rheumatic disease. Joint laxity is seen in 5-15% of healthy individuals without any symptoms, however may cause chronic pain complaints in certain individuals. Hypermobility syndrome has an important role in the etiopathogenesis of the soft tissue rheumatism and temporomandibular joint dysfunction syndrome. Impaired joint proprioception and excessive mobility may lead to ligament and joint capsule trauma in hypermobile patients. In addition, it's been suqqested that hypermobile subject, have high risk of mitral valve prolapsus, hernia, gynecological complications and osteoporosis by the advance of age. Evaluation of hypermobility on routine clinical practice will prevent unnecessary diagnostic workup and treatment modalities. A new diagnostic criteria set (Brighton 1998 criteria) revised from the widely accepted and used Beighton criteria, has been published recently. In the present article, clinical features related with the musculoskeletal system and visceral organ involvements in hypermobile subjects and novel approaches in diagnosis and treatment of the syndrome were reviewed.